Ζυμούμενο παραδοσιακό ρόφημα "Αϊρανι": Τεχνολογία και οργανοληπτικά χαρακτηριστικά - Ονουφρίου, Γιώργος (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
In the present study, was studied: a) the effect of adding pectin and b) using two different starter cultures on the physicochemical, organoleptic and rheological characteristics in ayran from sheep milk. Samples with pectin (0.2%) or without contained 60% yogurt, 40% water, 0.3% salt and 0.3% mint. The starter cultures used were YC-380 and YF-L812. The products were analyzed for the following parameters: chemical composition, pH, titratable acidity, serum separation, viscosity, TVC, LAB, coliforms, yeasts and molds and organoleptic characteristics. The results showed that the addition of pectin reduces serum separation to a minimum, while increases the viscosity. There was no significant difference in taste, odor, and acceptance of the product (p> 0,05). During the shelf life, pH decreases and titratable acidity increases. The lactic acid bacteria were at satisfactory levels for fermented milk products. The results showed that the chemical composition of the microbial flora, pH and acidity had no statistically significant differences (p> 0,05) between the four types of ayran.
Keywords: Fermented milk products; Ayran; Pectin; Viscosity; Ζυμούμενα προϊόντα γάλακτος; Αϊράνι; Πηκτίνη; Ιξώδες